Peri-Ulcerative Mucosal Inflammation Appearance is an Independent Risk Factor for 30-Day Rebleeding in Patients with Gastric Ulcer Bleeding: A Multicenter Retrospective Study - Bai Y; Lei C; Zhang N; Liu Y; Hu Z; Li Y; Qi R (Dove Medical Press, 2022)
Yixuan Bai,1 Chenggang Lei,2 Na Zhang,1 Yuhui Liu,1 Zhengyu Hu,3 Yan Li,4 Ran Qi5 1Department of Digestive Internal Medicine, Affiliated Dalian Friendship Hospital of Dalian Medical University, Dalian, People’s Republic of China; 2Department of Hepatobiliary Surgery, Qingdao Municipal Hospital, Qingdao, People’s Republic of China; 3Department of General Surgery, Shanghai Tenth People’s Hospital, Affiliated to Tongji University School of Medicine, Shanghai, People’s Republic of China; 4Department of Gastroenterology, Shanghai Tenth People’s Hospital, Affiliated to Tongji University School of Medicine, Shanghai, People’s Republic of China; 5Department of General Surgery, Tongji Hospital of Tongji University, School of Medicine, Tongji University, Shanghai, People’s Republic of ChinaCorrespondence: Ran Qi, Department of General Surgery, Tongji Hospital of Tongji University, School of Medicine, Tongji University, 389 Xincun Road, Putuo District, Shanghai, 200092, People’s Republic of China, Email 2011070@tongji.edu.cnAim: The aim of this study was to identify clinical endoscopic indicators related to peri-ulcerative mucosal inflammation and to analyze whether the degree of peri-ulcerative mucosal inflammation appearance is an independent risk factor for gastric ulcer rebleeding.Methods: We conducted a retrospective study that included patients with gastric ulcer bleeding who were hospitalized at three medical centers in China from January 1, 2016 to December 31, 2019. Ulcer rebleeding that occurred within 30 days of successful initial hemostasis was analyzed to determine whether this event was related to the degree of peri-ulcerative mucosal inflammation appearance or other mucosal inflammation-related factors.Results: We enrolled 1111 patients and determined that GBS-Rebleeding-ROC (P< 0.001), age (P=0.01), use of NSAIDs (P=0.001), bile reflux (P< 0.001), and Helicobacter pylori (P< 0.001) are all risk factors for peri-ulcerative mucosal inflammation appearance. Through multivariate analysis, we determined that severe peri-ulcerative mucosal inflammation appearance (P=0.002) was an independent risk factor for ulcer rebleeding within 30 days. Finally, we developed a risk assessment model using factors associated with mucosal inflammation that may be useful for early prediction of rebleeding.Conclusion: The risk factors for peri-ulcerative mucosal inflammation appearance were identified. Severe peri-ulcerative mucosal inflammation appearance is an independent risk factor for ulcer rebleeding.Keywords: gastric ulcer, peptic ulcer bleeding, risk factors, rebleeding, peri-ulcerative mucosal inflammation